2019
DOI: 10.1021/acschembio.9b00157
|View full text |Cite
|
Sign up to set email alerts
|

The Lasso Peptide Siamycin-I Targets Lipid II at the Gram-Positive Cell Surface

Abstract: Ribosomally synthesized post-translationally modified peptides (RiPPs) are a diverse class of biologically active molecules produced by many environmental bacteria. While thousands of these compounds have been identified, mostly through genome mining, a relatively small number has been investigated at the molecular level. One less understood class of RiPPs is the lasso peptides. These are 20−25 amino acid residue compounds bearing an N-terminal macrocyclic ring and a Cterminal tail that is threaded through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…Luciferase reporter assays. B. subtilis luciferase reporter assays were conducted as previously described 60 . Briefly, strains were grown in Mueller-Hinton broth at 30°C containing 5 µg ml −1 chloramphenicol until they reached an OD 600 of 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter assays. B. subtilis luciferase reporter assays were conducted as previously described 60 . Briefly, strains were grown in Mueller-Hinton broth at 30°C containing 5 µg ml −1 chloramphenicol until they reached an OD 600 of 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Two disulfide bonds containing linkages Cys1  Cys13 and Cys7  Cys19 form the tricyclic structure [22]. Recently, Tan et al [27] have found that siamycin I binds and inhibits the action of lipid II, the essential precursor molecule involved in peptidoglycan formation. Given the few differences in the amino acid sequences of class I lasso peptides, it might be also expected that other molecules of this group, including humidimycin, also inhibit peptidoglycan biosynthesis [27].…”
Section: Identification and Analysis Of Humidimycin Biosynthetic Genementioning
confidence: 99%
“…Importantly, only eight antibacterial lasso peptides have been connected to a cellular or molecular target; in most cases, the mechanisms of action remain obscure. Of the compounds that have been studied to date, the three main targets are RNA polymerase, ClpC 1 of the ClpC 1 P 1 P 2 protease complex and lipid II, the key precursor molecule of peptidoglycan [35,58,59] (Figure 5).…”
Section: Targets Of Lasso Peptidesmentioning
confidence: 99%
“…It was shown to activate the lia (lipid II-interfering antibiotics) operon, suggesting that it might impair peptidoglycan biosynthesis. A detailed analysis into siamycin-I’s target and mechanism of action was further pursued where it was found to bind and inhibit the action of lipid II, the essential precursor molecule involved in peptidoglycan formation [59].…”
Section: Targets Of Lasso Peptidesmentioning
confidence: 99%